Drone Technology to Enhance Healthcare Delivery Access - Gairolla, Jitender; Dobhal, Shivashish; Kumar, Vineet; Singh, Meenu (Indian Journal of Community Health, 2024)
Uttarakhand, a northern state in India is known for its rugged and mountainous terrain. This challenging landscape makes it difficult to deliver medical supplies, especially to the remote and hilly districts. Drones also referred to as unmanned aerial vehicles (UAVs) are increasingly being adopted in healthcare systems worldwide significantly improving access to medical services in remote and underserved areas. AIIMS Rishikesh has implemented drone technology in medical practice and organized a capacity-building program for health authorities, medical officers and other healthcare professionals to integrate drones into healthcare. Training health authorities to utilize drones in the healthcare system in challenging landscapes could enhance clinical and diagnostic services across the state.